ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA APBDES: Studi Kasus Desa Adabang Kecamatan Titehena Kabupaten Flores Timur - Kenale, Merviyati Masi; Herdi, Henrikus; Lamawitak, Paulus Libu (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to analyze financial ratios to assess village government performance through the 2020, 2021, and 2022 APBDes. The financial ratios used in this study are 5 ratios, namely the Village Independence Ratio, Harmony Ratio, Growth Ratio, Effectiveness Ratio and Efficiency Ratio . This study uses a Quantitative Descriptive method. The research data was obtained from the results of interviews, and documentation in the form of the 2020-2022 APBDes Realization Report. The results of the study show that the performance of the Adabang Village government from the aspect of the ratio of independence and the ratio of harmony is still very lacking. The growth rate of Adabang village is quite good and the level of effectiveness of Adabang village is already effective, while from the level of efficiency Adabang village is still not efficient.